ANALYSIS OF THE COURSE OF LABOR IN WOMEN, THE SECOND STAGE, WHICH WAS COMPLICATED BY SHOULDER DYSTOCIA - N. A. Udovika; S. N. Manischenkov; A. A. Leonov (Акушерство, гинекология и репродукция)
Purpose – analysis of the course of labor in 42 healthy primigravidas with a singleton full-term pregnancy to detect the risk of shoulder dystocia. All pregnancy came naturally. Indications for elective cesarean section was not. In 22 labor has begun its own, in 20 – induced. Risk of shoulder dystocia may be induction of labor, strengthening labor, lithotomy, early handling and vain attempts. The induction of labor should not be a routine method of delivery for the prevention of shoulder dystocia.